Analisis Mann-Whitney pada Pemahaman Materi Statistika Pendidikan - Mufarrikoh, Zainatul (CV. Creative Tugu Pena, 2024)
Educational statistics is a compulsory subject taught in every study program of the Faculty of Tarbiyah. This study aims to analyze student understanding and differences between understandings of the two study programs. The respondents were students who had taken educational statistics, who came from the Islamic Education Management (MPI) and Early Childhood Islamic Education (PIAUD) study programs, Faculty of Tarbiyah IAIN Madura. Respondents were taken using stratified random sampling techniques. The statistical test method used is a nonparametric test, namely the mann-whitney test. The results of the study are important information for researchers in improving learning in the future. Analysis of understanding is seen from student learning outcomes for each study program, and differences in understanding between the two study programs. Based on descriptive statistics, it was obtained that the understanding of statistical material in the MPI study program was most widely found in descriptive statistical material, while the PIAU study program in inferential statistics, the difference in student material understanding was obtained that the MPI study program was better than the PIAUD study program. This is obtained from the p-value in the mann-whitney test is smaller than the error rate value of 5%. The conclusion of the mann-whitney test was obtained that the average score in the MPI study program was greater than the average score in the PIAUD study program. Keywords: Educational Statistics, Analisis Mann-Whitney, Educational Statistics Material